Institutional practices : a key factor for improving school effectiveness - Brígido, Ana María (2013)
Fil: Brígido, Ana María. Universidad Nacional de Córdoba. Facultad de Filosofía y Humanidades. Escuela de Ciencias de la Educación; Argentina.